2022
DOI: 10.3390/vaccines10101753
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Inactivated COVID-19 Vaccines against COVID-19 Caused by the SARS-CoV-2 Delta and Omicron Variants: A Retrospective Cohort Study

Abstract: Background: Real-world evidence on the effectiveness of inactivated vaccines against the Delta and Omicron (BA.2.38) variants remains scarce. Methods: A retrospective cohort study was conducted to estimate the adjusted vaccine effectiveness (aVE) of one, two, and three doses of inactivated vaccines in attenuating pneumonia, severe COVID-19, and the duration of viral shedding in Delta and Omicron cases using modified Poisson and linear regression as appropriate. Results: A total of 561 COVID-19 cases were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“… 1–2 - 5–8 The two-dose (mRNA and inactivated vaccines) VEs were reported to be 50.5–74.6% against the Delta variant infection and 0–44% against the Omicron variant infection. 9–15 Limited data showed that the three-dose (mRNA vaccines) VE was 86.0–93.7% against the Delta variant infection and 7–47.4% against the Omicron variant infection. 15–17 These findings confirmed the substantially decreased protection from the booster dose against the Omicron variant infection.…”
Section: Introductionmentioning
confidence: 99%
“… 1–2 - 5–8 The two-dose (mRNA and inactivated vaccines) VEs were reported to be 50.5–74.6% against the Delta variant infection and 0–44% against the Omicron variant infection. 9–15 Limited data showed that the three-dose (mRNA vaccines) VE was 86.0–93.7% against the Delta variant infection and 7–47.4% against the Omicron variant infection. 15–17 These findings confirmed the substantially decreased protection from the booster dose against the Omicron variant infection.…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID- 19) was first reported in December 2019 and then rapidly spread to the rest of the world. The World Health Organization (WHO) declared the COVID-19 pandemic on 11 March 2020.…”
Section: Introductionmentioning
confidence: 99%
“…A large amount of evidence has indicated that vaccinations are particularly effective in reducing the incidence of severity and mortality among COVID-19 patients [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. To date, more than 200 COVID-19 vaccine candidates are in various stages of development, and more than 50 of these candidates have started clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…As of 26 October 2022, 624 million patients have been confirmed with the COVID-19 diagnosis globally of which 6.5 million patients have died [ 1 ]. Vaccines have shown to be very effective against severe COVID-19 disease and mortality [ 2 , 3 , 4 , 5 , 6 , 7 ]; it is also important to understand risk factors (e.g., to decide whom to prioritize for vaccination). Until now, several variables (age, sex, and certain past medical history) have been identified as risk factors for COVID-19 mortality [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%